Implementation of Collaborative Learning Method to Enhance Critical Reading Skills of An-Annadhliyyah Sooko Students - Jayanti, Rani; Romadhona, Ahlan; Fitri, Aini; Auliyah, Kartika; Sari, Martha Amanda; Ardiansyah, M. Afif (Universitas PGRI Sumatera Barat, 2024)
Improving critical reading skills is considered important in today's education. One promising approach in this regard is the collaborative learning method. The purpose of this study is to find out how effective collaborative learning is in improving students' critical reading skills at An-Annadhliyyah Sooko. The research was conducted using descriptive analysis method, in which data was collected through observation, interview, and document analysis. The results showed that students' critical reading skills, their desire to learn, and their social skills had all been improved when collaborative learning methods were used. Nonetheless, some challenges such as time management and the development of teachers' facilitation skills need to be addressed. To improve student achievement and learning quality in the future, schools and teachers should continue to encourage and improve the application of collaborative learning methods.